ATTENTION DEFICIT HYPERACTIVITY DISORDER (ADHD) IN ADULTS: AN OVERVIEW OF THE CURRENT STATE OF KNOWLEDGE, DIAGNOSTIC CHALLENGES, AND THERAPEUTIC STRATEGIES - Igor Winogrodzki; Bartłomiej Trzciński; Patryk Kowalczyk; Oliwia Gugała; Alicja Stryczek-Schlusche; Aleksandra Magdalena Furczyńska; Filip Bracichowicz; Aleksandra Gęsińska; Hanna Paszkiewicz; Kamil Nowak (International Journal of Innovative Technologies in Social Science, 2025)
Attention Deficit Hyperactivity Disorder (ADHD) is a neurodevelopmental disorder most commonly diagnosed in childhood. In recent years, the approach to its diagnosis and understanding has undergone significant changes. ADHD is increasingly being diagnosed in adulthood, which is related to advances in diagnostics and growing awareness among specialists. The aim of this review is to present the current state of knowledge regarding the clinical picture, diagnostic methods, and therapeutic strategies used in the treatment of ADHD in adults. The most common comorbid disorders and difficulties resulting from late diagnosis of this condition will also be discussed. Attention was also drawn to the need for further research and the development of specialist education in the diagnosis of ADHD.